Mutation of Trp-574-Leu ALS gene confers resistance of radish biotypes to iodosulfuron and imazethapyr herbicides - Cechin, Joanei (2017)
Acetolactate synthase inhibitors are the main group of herbicides used in winter crops in Southern Brazil where their intensive use has selected for herbicide-resistant biotypes of radish. The resistance affects the efficacy of herbicides, and identifying the resistance mechanism involved is important for defining management strategies. The aim of this study was to elucidate the resistance mechanism of radish biotypes by quantifying the enzyme activity, ALS gene sequencing and evaluating the response of biotypes to iodosulfuron and imazethapyr herbicide application after treatment with a cytochrome P450 monooxygenase inhibitor. The susceptible (B1) and resistant (B4 and B13) biotypes were from wheat fields in the Northwest of Rio Grande do Sul State. The results demonstrated that the enzyme affinity for the substrate (KM) was not affected in biotypes B4 and B13 but that the Vmax of the resistant biotypes was higher than that of biotype B1. The resistant biotypes showed no differential metabolic response to iodosulfuron and imazethapyr herbicides when inhibited by malathion and piperonyl butoxide. However, gene sequencing of ALS showed a mutation at position 574, with an amino acid substitution of tryptophan for leucine (Trp-574-Leu) in resistant biotypes.